Характеристика основних правових та політико-кон’юнктурних факторів політичної злочинності в Україні - Орлов, Ю. В.; Orlov, Y. V.; Орлов Юрій Володимирович (Юридичний науковий електронний журнал. - 2018. - № 5. - С. 177-180, 2018)
Надано кримінологічний аналіз основних правових та політико-кон’юнктурних факторів політичної злочинності в Україні. Обґрунтовано криміногенний характер невідповідності ціннісної основи правового імперативу у різних груп населення, державах. Наголошено на криміногенній ролі прогалин у регулюванні лобістської діяльності, кримінологічного супроводження правотворчого процесу, порядку формування виборчих списків партій, а також порядку верифікації, ідентифікації текстів законопроектів. Акцентовано увагу на криміногенності впливу організованих злочинних угруповань на політичний процес. The article is devoted to criminological analysis of legal and political-conjunctural factors of political crime in Ukraine. It substantiates principal elements of the mechanism of crimogenic determination triggered by: a) discrepancy between legal imperative and values in the sphere of public interest of a certain, conditionally considerable part of state population; b) discrepancy between value basis of legal imperative of one state and ideological principles of legal regulation of the other state. The article emphasizes criminogenic role of lacunas in regulation of lobbying, criminological support of law-making process, the procedure of the formation party electoral lists, as well as the procedure of verification, identification of texts of bill, put to a vote at the session of the Verkhovna Rada of Ukraine and texts of laws, signed by the Speaker of the parliament and sent forthe signature ofthe President of Ukraine. The article ascertains that character and intensity of political-conjunctural factors of political crime depend on a number of factors: a) existence of objective preconditions for destabilization of social-political situation (deterioration of economical, social, ecological problems etc.); b) quantity and financial potential of political opposition, their strategic and tactic objectives, orientation, links (economical, political) with foreign subjects - states, organizations, corporations etc.; c) the level of political and general culture of bureaucratic (including political and economical) elite, its links with organized criminal groups; d) the level of public political culture; e) the state of functional efficiency of law enforcement organs. The article emphasizes criminogenic significance of the impact of organized criminal groups on political process. It ascertains that politi-cal-conjunctural and criminal-conjunctural correlation of state (in a certain historical period) and local elites has a substantive influence on the character, directions and forms of such impact. The article substantiates that the factors of establishing, nourishing of separatist movement are expedited by the tendencies of preserving or establishing (redistribution) of criminal impact on certain territories under the threat of its elimination in novel conditions or at list substantial change of its configuration in favour of other subjects. Представлен криминологический анализ основных правовых и политико-конъюнктурных факторов политической преступности в Украине. Обоснован криминогенный характер несоответствия ценностной основы правового императива в разных группах населения, государствах. Отмечена криминогенная роль пробелов в регулировании лоббистской деятельности, криминологического сопровождения правотворческого процесса, порядка формирования избирательных списков партий, а также порядка верификации, идентификации текстов законопроектов. Акцентировано внимание на криминогенности влияния организованных преступных группировок на политический процесс.
Characteristics of the main legal and political-contingency factors of political crime in Ukraine
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; злочинність; преступность; criminality; політична злочинність; политическая преступность; political crime; детермінація; детерминация; determination; правові фактори злочинності; правовые факторы преступности; legal factors of crime; політико-кон'юктурні фактори злочинності; политико-конъюнктурные факторы преступности; political and conjunctural factors of crime; правове регулювання; правовое регулирование; legal regulation; прогалина; пробел; конфлікт; конфликт; conflict